If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4x + 12) = (6x + -12) Reorder the terms: (12 + 4x) = (6x + -12) Remove parenthesis around (12 + 4x) 12 + 4x = (6x + -12) Reorder the terms: 12 + 4x = (-12 + 6x) Remove parenthesis around (-12 + 6x) 12 + 4x = -12 + 6x Solving 12 + 4x = -12 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 12 + 4x + -6x = -12 + 6x + -6x Combine like terms: 4x + -6x = -2x 12 + -2x = -12 + 6x + -6x Combine like terms: 6x + -6x = 0 12 + -2x = -12 + 0 12 + -2x = -12 Add '-12' to each side of the equation. 12 + -12 + -2x = -12 + -12 Combine like terms: 12 + -12 = 0 0 + -2x = -12 + -12 -2x = -12 + -12 Combine like terms: -12 + -12 = -24 -2x = -24 Divide each side by '-2'. x = 12 Simplifying x = 12
| f(x)=lx+2l-x | | 6[3x+7]=78 | | 5/2x-17=48 | | f(3)=6(3)-9 | | -2x-12=2x-12 | | log[3](4x-2)=2 | | 2[-7x-8]=82 | | x^2(x^4+16)-8x^4=0 | | (2x-4)*ln(x-1)=0 | | 13v-9v=24 | | 4x+72=12x+16 | | 36/24=15/x | | G-4v+10v=14 | | 15=-6-3x | | 7[4x+7]=161 | | 4y-3+y+53=7y+50-5y | | 24x+5=26x-5 | | -1-7x=20 | | 12.5/16 | | -5x-2=38 | | 6+2p-2=7p+4-4p | | 2n-1+n+-5=3n-1+n | | F(0)=15(0)-10 | | 3(4x+6)=34x-6 | | d=3+0.25d | | x+-5+1= | | 55x=70(x+30) | | 500t=700(60+t) | | 3975+6d=995+17.95d | | 32-6x=8+2 | | 16x=6y | | -8j+14=-8j+14 |